2009
DOI: 10.1111/j.1475-1313.2009.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation response and visual discomfort

Abstract: Although visual discomfort symptoms associated with near work have been correlated with clinical measures of accommodation, studies using objective recordings have not found corresponding deficits in accommodative function. One problem with previous studies is that accommodation measures have been too brief to assess accommodative fatigue. This study examined steady state accommodative responses among a college population with visual discomfort, over a 90-s time period. Thirty-one participants were grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 41 publications
7
100
2
1
Order By: Relevance
“…Tosha et al (2009) found that participants with high visual discomfort showed significant signs of fatigue when the distance of the target was 4D compared to 2D. Chase et al (2009) also found larger lags in those with high visual discomfort when viewing targets at 4-5D.…”
Section: Experiments 4 Accommodation To Different Spatial Frequency Grmentioning
confidence: 82%
See 3 more Smart Citations
“…Tosha et al (2009) found that participants with high visual discomfort showed significant signs of fatigue when the distance of the target was 4D compared to 2D. Chase et al (2009) also found larger lags in those with high visual discomfort when viewing targets at 4-5D.…”
Section: Experiments 4 Accommodation To Different Spatial Frequency Grmentioning
confidence: 82%
“…Tosha et al (2009) found effects of fatigue between individuals with high and low visual discomfort after 60 seconds of viewing the stimulus. However, when using the Pattern Glare Test (which measures the number of illusions reported in grating patterns that vary in their spatial frequency) each pattern is only presented to the participant for 3 seconds (Wilkins & Evans, 2001), and yet individuals report discomfort and illusions.…”
Section: Interim Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accommodative fluctuations have been reported to be greater in individuals who experience visual distortions and benefit from coloured filters. 18 The accommodative lag is greater in individuals who report visual discomfort 19,20, and pattern glare, 21 although these differences may take time to appear and be more apparent at close viewing distances. 20 Close viewing distances affect not only accommodation but also vergence.…”
mentioning
confidence: 99%